Acessibilidade urbana por ride-hailing e transporte público considerando o trade-off entre custo monetário e tempo de viagem - Rafael Henrique Moraes Pereira; Daniel Herszenhut; Marcus Saraiva; Steven Farber (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– Ride-hailing services have the potential to expand access to opportunities, but out-of-pocket costs may limit the benefits of ride-hail for low-income individuals. This paper examines how ride-hailing services can shape spatial and socioeconomic differences in access to opportunities while accounting for the trade-off between travel time and monetary costs. Using one year of aggregated Uber trip data for Rio de Janeiro in 2019 and a new multi-objective optimization routing method, we analyze the potential for ride-hailing services to improve employment accessibility when used as a standalone transportation mode and in conjunction with transit as a first-mile feeder service. We compare the accessibility Pareto frontiers of these transport mode alternatives with cumulative opportunity measures considering multiple combinations of travel time and monetary cost thresholds. We find that, compared to transit, ride-hailing can significantly expand accessibility as a standalone transport mode for relatively short trips (between 10 and 40 minutes), and as a first-mile feeder to transit in trips longer than 30 minutes. In both cases, the accessibility advantages of ride-hailing are mostly limited by relatively higher out-of-pocket costs. When we account for different affordability thresholds, the accessibility benefits of ride-hailing services accrue mostly to high-income groups. These findings suggest that policy efforts to integrate rideshare with transit are likely not going to benefit low-income communities without some form of subsidized fare discounts to alleviate affordability barriers. The paper also highlights how accounting for trade-offs between travel-time and monetary costs can importantly influence the results of transportation accessibility and equity studies, suggesting that this issue should be addressed in future research.
Keywords: O18; R40; R41; 330; ride-hailing; accessibility; equity; monetary cost; Rio de Janeiro; first-mile transit; affordability; Pareto frontier